Phenological And Growth Analysis of 45 Winter Wheat Varieties in Khorezm Region: Insights from Crop Growth Parameters - Raximova Go'zaloy Quvondiq qizi (Scientific Trends, 2025)
Winter wheat is a staple crop in the Khorezm region of Uzbekistan, playing a critical role in ensuring regional food security and economic stability. The region’s agricultural productivity is heavily dependent on efficient management of natural resources and the selection of optimal cultivars suitable for its unique agroecological conditions. Despite its importance, variability in yield outcomes often arises due to differences in cultivar performance, climatic conditions, and management practices. Addressing these challenges requires a thorough understanding of the growth dynamics and phenological characteristics of winter wheat varieties